Effect of Chemical and Physical Properties of River Water in Shatt Al-Hilla on Phytoplankton Communities - Fikrat M. Hassan; Nuha F. Kathim; Falah H. Hussein (E-Journal of Chemistry)
This paper aims to study the chemical and physical properties in the ecological system of Shatt Al-Hilla in Babylon Governorate in Iraq and its effect on phytoplankton population. In this context, several limnological parameters were evaluated during the period from December 2003 through November 2004 from four sampling stations sited along Shatt Al-Hilla. The physical parameters included: temperature, turbidity and electrical conductivity. The chemical parameters included: pH, alkalinity dissolved oxygen, total hardness and the concentrations of nitrite, nitrate, phosphate and sulphate. A total of 154 species were recorded. Ninety-seven species of the total belong to Bacillariophyceae, 37 species belong to Chlorophyceae, 13 species to Cyanophyceae, 5 species to Chrysophyceae, and 2 species to Euglenophyceae. Bimodal variation of phytoplankton was observed. Five genus of phytoplankton were the highest number of species ( Nitzschia, Navicula, Gomphonema, Cymbella and Scendesmus). Some species was occurred continuously during study period such as, Cyclotella ocellata, Cyclotella meneghiniana, Aulacoseria distans, and Gomphonema abbreviatum. The phytoplankton communities at all sampling sites showed a clear seasonal variation in phytoplankton cell number. However, no significant correlation between total cell number of phytoplankton and nutrient concentration was observed. The study was revealed the city sewage discharge, agriculture and urban run-off were affecting the water quality of Shatt Al-Hilla.